Low profile multiband rectenna for efficient energy harvesting at microwave frequencies. Issue 12 (2nd December 2019) - Singh, Neeta; Kanaujia, B. K.; Beg, M. T.; Mainuddin,; Kumar, Sachin; Choi, Hyun Chul; Kim, Kang Wook
ABSTRACT: This paper presents the design and development of a multiband rectenna for ambient RF energy harvesting. The proposed rectifying antenna consists of fractal-based geometry to obtain GSM 0.9 GHz (0.8–1.2 GHz), GSM 1.8 GHz (1.6–2.1 GHz), WLAN 2.5 GHz (2.2–2.8 GHz), Wi-MAX 3.5 GHz (3.1–4.0 GHz), WLAN 5.5 GHz (5.3–6.4 GHz) and 7.35 GHz (7.0–7.8 GHz) resonating bands. The designed sensing antenna is low profile, lightweight and small in size with two circularly polarized bands at frequencies 1.8 and 2.5 GHz. In the proposed rectenna, a dual-stage voltage doubler rectifying circuit is utilized for converting surrounding RF signals into DC power. A matching network is connected between the fractal antenna and the rectifying circuitry for realizing a good impedance matching between them. To verify the proposed design, a prototype rectenna is fabricated and measured results are compared with the simulated results. The proposed rectifier provides an RF to DC conversion efficiency of 78%.